Features of the Propagation of the Ascospores of the Sunflower Phomopsis Blight Pathogen in the Surface Layer of the Atmosphere in the Conditions of the South of Russia - M. Androsova, Valentina; О. Didenko, Аnton; T. Podvarko, Aleksandr; P. Esipenko, Leonid (International Journal of Psychosocial Rehabilitation, 2020)
The present article focuses on the features of the propagation of ascospores of the sunflower phomopsis pathogen in the surface layer of the atmosphere, depending on meteorological conditions, taking into account the development of the fungus in pure culture and on sunflower mulch in southern Russia. The maximum average growth of the mycelium of the fungal isolates transferred to the pure culture from the diseased sunflower stems harvested in different regions of southern Russia was observed at temperatures of 25 and 30°C, between which no statistically significant differences were found. The minimum mycelium growth was detected at a temperature of 32°C; its average value was statistically significantly different from the two previous temperatures. However, both at 30°C and at 32°C, pycnidia did not form, and, therefore, perithecia could not form either. Ascospores, propagating from an artificially created focus of infection, were detected in sunflower crops with the help of special spore traps. It was established that the propagation of ascospores of the sunflower phomopsis pathogen in the surface layer of the atmosphere depended on the degree of infection development on the plant mulch as well as on hydrothermal environmental factors. The propagation started 1-3 days after even minimal precipitation (0.05 mm or less) in a wide range of average daily relative humidity (38-80% or more), at an average daily temperature (13-30°C) and hydrothermal coefficient of more than or equal to or less than 1. The largest number of days with the presence of ascospores in the surface layer of the atmosphere was at the highest relative humidity (66-80 % and more). Prolonged atmospheric and soil droughts that had a particularly dangerous duration (the drought lasted 45 days), accompanied by elevated daily average temperatures (30°C or more) during the growing season of sunflowers, followed by severe, snowless winter periods, led to the death and cessation of pycnidia formation. However, these phenomena initiated a significant increase in the number of ascospores in the surface layer of the atmosphere. Abnormally high average daily temperatures (30 °C or more) and relative air humidity from 38 to 50% during the growing season of sunflowers led to a significant decrease in the propagation of infection.